PERAN DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA DALAM KONSERVASI SUMBER DAYA ALAM BERDASARKAN UNDANG-UNDANG NOMOR 27 TAHUN 2009 (STUDI KASUS DI JAWA TENGAH) - Ratna Herawati (Faculty of Law, Universitas Diponegoro, 2011)
Natural Resources represent the element from environment. Environmental crisis as its uneven effect of natural resources exploiting bear the opinion to do the conservation. The House of Regional Representative of the Republik of Indonesia as representative institute fighting for area aspiration have the rule of related to natural resources conservation. The role is pursuant to article 220 paragraph (1 ), (2) and (3) Constitution of State of Republik Indonesia of 1945 that covering legislation and oversight functions and also considerations function. Therefore this research is conducted to findout the role of The House of Regional Representative of the Republik of Indonesia and solution for the problems relating to the management of natural resources, specially in Middle Java.